Effect of homogenization associated with alkaline treatment on the structural, physicochemical, and emulsifying properties of insoluble soybean fiber (ISF). (April 2021) - Cai, Yongjian; Huang, Lihua; Chen, Bifen; Su, Jiaqi; Zhao, Xiujie; Zhao, Mouming; Zhao, Qiangzhong; Van der Meeren, Paul
Abstract: Comprehensive utilization of okara has received a growing interest from manufacturers and researchers in the food industry. In this work, ISF was extracted from defatted okara in the sequence of "homogenization followed by pH12 treatment" and "pH12 treatment followed by homogenization", which are indicated as HA-ISF and AH-ISF, respectively; Subsequently, the basic properties and initial structure of these ISFs, as well as their emulsification performance were systematically characterized. The results indicated that as the homogenization intensity was enhanced, more negatively charged, smaller particle as well as porous structures were detected in the extracted ISF. The size of oil droplets in ISF-emulsions decreased and then increased, the absolute value of the ζ-potential and the loss angle (tan δ) were reduced, the apparent viscosity and elastic modulus (G′) increased, and the flocculated structure in the ISF-emulsions was promoted as the homogenization intensity was increased. Creaming in the ISF-emulsions was effectively inhibited by homogenization via adsorption of ISF onto the interface and network stabilization. More obvious aforementioned changes were observed in AH-ISF than HA-ISF, as well as in the corresponding emulsions. These results provided valuable information for the exploitation of ISF as emulsifier, which is a promising approach to enhance the added-value of okara . Graphical abstract: Image 1 Highlights: The extracting sequence affected physicochemical properties of insoluble soybean fiber (ISF). Alkali-treatment followed by homogenization changed physicochemical properties of ISF, thereby improving it's emulsifying characteristics. A combination of interparticle interaction and network stabilization contributed to forming and stabilizing ISF-emulsions.